Design, synthesis and evaluation of activity and pharmacokinetic profile of new derivatives of xanthone and piperazine in the central nervous system. Issue 21 (1st November 2019) - Żelaszczyk, Dorota; Jakubczyk, Magdalena; Pytka, Karolina; Rapacz, Anna; Walczak, Maria; Janiszewska, Paulina; Pańczyk, Katarzyna; Żmudzki, Paweł; Słoczyńska, Karolina; Marona, Henryk; Waszkielewicz, Anna M.
Graphical abstract: Abstract: Searching for CNS active cyclic amines derivatives containing heterocyclic xanthone core we designed and synthesized a set of fourteen novel 2- or 4-methylxanthone substituted by alkyl- or aryl-piperazine moieties. The compounds were evaluated in vivo for their potential antidepressant-like activity (in the forced swim test) and anxiolytic-like activity (four-plate test) and their inhibitory effect against rat 5-HT2 receptor was checked. The pharmacokinetic analysis of active compounds done by a non-compartmental approach have shown a rapid absorption of all studied molecules from intraperitoneal cavity and good penetration the blood-brain barrier after i.p. administration with brain to plasma ratios varied from 2.8 to 31.6. Genotoxicity and biotransformation of active compounds were studied. Compound19 interactions with major classes of GPCRs, uptake systems and ion channels were tested and results indicated that it binds to 5-HT2A, 5-HT2B receptors and sodium channels.